Pemberdayaan Majelis Taklim Melalui Edukasi Ekologi Qur'ani Berbasis Geografi Lokal di Bulan Ramadhan - Raudatussolihah, Baiq; Kholida, Masita Taufiqi; Perdana, Dyah Adila; Susiawati; TM, Ahmad Rais (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to empower majelis taklim through Qur'anic ecological education that is relevant to the local geography. The activity was carried out during the month of Ramadan, a strategic moment to enhance spiritual and environmental awareness. The education focused on understanding the Qur'anic verses related to the environment and their application in the local community context. The method of service employed a participatory qualitative approach, involving the administrators and members of the majelis taklim. The results showed an increase in contextual ecological understanding and awareness. This proves that the integration of Qur'anic values with the local geographical context can be an effective educational strategy.